1981
DOI: 10.1203/00006450-198104001-00713
|View full text |Cite
|
Sign up to set email alerts
|

690 the Increased Frequency of Henoch Shoenlein Purpura in Familial Mediterranean Fever

Abstract: obscured because these terms a r e often used interchangeably. A l l cases of PC and OC with a positive blood,tissue a s p i r a t e , o r abscess culture seen a t Children's o r Eye and Ear Hospital i n the past 10years were analyzed. Results (including median age): TOTAL H.influenzae B(H1B) S.pneumoniae(SP) Other bacteria -PC 61 57% (15 mos) 18% (12 mos) 25% (6 y r s ) OC 10 0% 0% 100% (11 yrs) PC caused by HIB and SP, characterized by bacteremia, fever and p e r i o r b i t a l swelling, discoloration, indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Given that, most of the FMF-associated vasculitis cases had MEFV gene mutations, contributing role of these mutations for vasculitis development may be considered in the pathogenesis. In line with this view, our literature search showed that most of the FMF patients reported in literature with coexistent HSV or PAN had [7,9,10,13,14,65,66] Medium vessel vasculitic diseases Polyarteritis nodosa [7, 8, 11-13, 15, 70, 71] Large vessel vasculitic diseases Unreported Unclassified vasculitic conditions Protracted febrile myalgia [16,60,[72][73][74] Behçet's disease [17,18,79] Cutaneous vasculitis [87,88] either homozygous or compound heterozygous M694V mutations. However, since many FMF patients carrying these mutations do not have associated vasculitis, we admit that this coexistence cannot solely be explained by the presence of MEFV gene mutations.…”
Section: Pioneering Reports About Fmf-vasculitis Associationmentioning
confidence: 57%
See 2 more Smart Citations
“…Given that, most of the FMF-associated vasculitis cases had MEFV gene mutations, contributing role of these mutations for vasculitis development may be considered in the pathogenesis. In line with this view, our literature search showed that most of the FMF patients reported in literature with coexistent HSV or PAN had [7,9,10,13,14,65,66] Medium vessel vasculitic diseases Polyarteritis nodosa [7, 8, 11-13, 15, 70, 71] Large vessel vasculitic diseases Unreported Unclassified vasculitic conditions Protracted febrile myalgia [16,60,[72][73][74] Behçet's disease [17,18,79] Cutaneous vasculitis [87,88] either homozygous or compound heterozygous M694V mutations. However, since many FMF patients carrying these mutations do not have associated vasculitis, we admit that this coexistence cannot solely be explained by the presence of MEFV gene mutations.…”
Section: Pioneering Reports About Fmf-vasculitis Associationmentioning
confidence: 57%
“…Schlesinger et al [10] also reported this association from Israel in 1985. Then, Ozdogan et al [7] from Turkey retrospectively reviewed the charts of their series of 207 FMF patients and found out 15 patients with HSP, corresponding to the frequency of 7.2%.…”
Section: Pioneering Reports About Fmf-vasculitis Associationmentioning
confidence: 79%
See 1 more Smart Citation
“…Joint involvement in children can masquerade as various other pediatric arthritides [26,45]. In 10 to 70% of cases, dermatological abnormalities are present; these consist most commonly of erysipelas-like lesions [6,12,46,47] which involve the legs, ankles, and dorsum of the feet. Other manifestations are nodular rashes, Schonlein-Henoch purpura [5,46,47], urticaria [6,47], bullous lesions [48], and a vasculitis which is usually associated with an immune-complex nephropathy [49].…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…In 10 to 70% of cases, dermatological abnormalities are present; these consist most commonly of erysipelas-like lesions [6,12,46,47] which involve the legs, ankles, and dorsum of the feet. Other manifestations are nodular rashes, Schonlein-Henoch purpura [5,46,47], urticaria [6,47], bullous lesions [48], and a vasculitis which is usually associated with an immune-complex nephropathy [49]. In addition, splenomegaly is present in about 30% of cases overall [11][12][13] and, like the arthropathy and dermatological lesions, is less frequent in Arab patients [18].…”
Section: Clinical Aspectsmentioning
confidence: 99%